2019
DOI: 10.1155/2019/4845729
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Accuracy of a Flash Glucose Monitoring System in Children with Diabetes in comparison with Venous Blood Glucose

Abstract: Aims. To evaluate the performance of a factory-calibrated flash glucose monitoring system in children with diabetes compared to venous blood glucose (BG). Methods. A total of 13 hospitalized participants newly diagnosed with type 1 diabetes, aged 1~14 years old, were involved in the study. Sensor glucose measurements on days 2, 3, 6, 7, 12, and 13 of wear were compared with venous BG. During these days, the venous BG results were obtained either 4 or 7 times per day. Results. The accuracy was evaluated against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…The accuracy of FGM may play a role in this setting, even though a higher mean absolute relative difference has generally been reported during hypoglycemia rather than hyperglycemia. [27][28][29] It is worth noting that the definition of hypoglycemia differed among the included studies. According to current guidelines, it should be defined as any measurable glucose concentration <70 mg/dL, either symptomatic or asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of FGM may play a role in this setting, even though a higher mean absolute relative difference has generally been reported during hypoglycemia rather than hyperglycemia. [27][28][29] It is worth noting that the definition of hypoglycemia differed among the included studies. According to current guidelines, it should be defined as any measurable glucose concentration <70 mg/dL, either symptomatic or asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…The senor values were mostly lower than those of the capillary BG, and the difference gradually increased with the increase of BG levels. Different studies have debated whether there is a lag effect between the FreeStyle ® Libre System values and capillary BG values 5,16 ; therefore, we performed a detailed difference analysis at different time points (0, 5, 10, and 15 min) and different BG levels. Our results showed a gradual increase in the MARD over time, suggesting the lag time was short.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies [5][6][7][8][9][10] have demonstrated the benefits of the FreeStyle ® Libre Glucose Monitoring System, which includes helping reduce hemoglobin A1c (HbA1c) levels and hypoglycemic episodes and increase the target range time in children and adult populations. However, most of the trials were conducted on children aged >4 years, and there is limited data on children aged <4 years, including infants, with diabetes mellitus.…”
mentioning
confidence: 99%
“…Although most studies have shown that isCGM systems are within a safe clinical range [10][11][12] conclusive large-scale assessments of isCGM performance and the impact of the rate of change in glucose are currently lacking. Therefore, the aim of this pooled analysis was to assess isCGM (FreeStyle Libre 1; Abbott Diabetes Care, Alameda, California) performance and the rate of change in sensor glucose in a cohort of children, adolescents, and adults with type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%